Growth and feeding of Patagonian pejerrey Odontesthes hatcheri reared in net cages - Hualde, Juan Pablo (2011)
An experimentwas performed to evaluate the performance of Patagonian pejerrey during net cage rearing in the oligomesotrophic reservoir Exequiel Ramos Mex|¤a. Survival, growth, nutrition and reproduction were evaluated for two lots of pejerrey, initial weights 4.0 and 2.5 g, reared in net cages for 22 and 14 months respectively. Fish were stocked at 29 and 48 individualsm3 densities and fed with an experimental pejerrey feed. During the experiment, temperature £uctuated between 6.6 and19.6 1C. The two lots did not show substantial di¡erences in survival (pooled survival at the end of the experiment 480%) and the thermal-unit growth coe⁄cient (TGC), daily feed intake and feeding e⁄ciency were 0.43 0.19, 1.70 0.80 and 53.6 9.9 respectively. Digestive tract analysis showed that caged pejerrey can consume substantial quantities of natural food, taking advantage of its planktivorous condition. Pejerrey showed high percentage survival, slow growth and early sexual maturation in captivity. The use of the TGC is proposed as a model for describing the growth pattern of this species and other pejerrey under culture conditions.